The human rights defenders in post-EDSA Phillippines - Gultia, Christian
The study seeks to analyze the work of human rights defenders and their contribution to transitional justice efforts in the Philippines. It presents a recap of the different situations of human rights defenders in the years following the end of the Marcos dictatorship - from the government of President Corazon Aquino to the administration of President Rodrigo Roa Duterte. It outlines the issues, challenges, and milestones in terms of transitional justice in the Philippines, and how human rights defenders as part of the civil society movement, contributed to the process.